Postępowanie dowodowe w przypadku usprawiedliwionej nieobecności oskarżonego lub obrońcy (art. 378a Kodeksu postępowania karnego) - Piech, Michał (Czasopismo Prawa Karnego i Nauk Penalnych, 2020)
The article presents the normative analysis of Article 378a of the Code of Criminal Procedure (k.p.k.) and discusses the following issues: the premises for, and the scope of evidentiary proceedings in the event of a justified absence of the accused or defence counsel, and the grounds for an appeal against the court’s decision on the application of this mode of proceedings. The above-mentioned Article is also analyzed in the context of constitutional standard (i.e. Article 42 Section 2, Article 45 Section 1, Article 2, and Article 31 Section 3 of the Polish Constitution) and the case-law of the European Court of Human Rights. These considerations are supplemented by an examination of possible threats to procedural guarantees arising from the application of Article 378a k.p.k., as well as with de lege ferenda postulates. In summary, the author gives his assessment of the provision in question.